2015
DOI: 10.1093/cid/civ739
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal-Associated Drug-Induced Cardiac Disease

Abstract: The etiology of cardiomyopathies are classified into 4 main groupings (dilated, hypertrophic, restrictive, and idiopathic) and can be mechanistically caused by myocarditis, conduction abnormalities, focal direct injury, or nutritional deficiency. Based on our review of this topic, evidence suggests that echinocandin-related cardiac dysfunction is a mitochondrial drug-induced disease caused by focal direct myocyte injury. With caspofungin or anidulafungin administration into the heart via central line, exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…However, recent data raise doubts about their safe use in critically ill patients with regard to hemodynamic stability (14)(15)(16). Several cases of severe hemodynamic instability following echinocandin infusion were reported, which led to the definition of an antifungal-associated drug-induced cardiac disease by Cleary et al (4)(5)(6)11). Cardiac impairment following echinocandin administration was reported in isolated rat cardiomyocytes (3).…”
mentioning
confidence: 99%
“…However, recent data raise doubts about their safe use in critically ill patients with regard to hemodynamic stability (14)(15)(16). Several cases of severe hemodynamic instability following echinocandin infusion were reported, which led to the definition of an antifungal-associated drug-induced cardiac disease by Cleary et al (4)(5)(6)11). Cardiac impairment following echinocandin administration was reported in isolated rat cardiomyocytes (3).…”
mentioning
confidence: 99%
“…While drugs within all 4 classes of systemic antifungals (azoles, polyene macrolides, allylamines, and echinocandins) have shown cardiovascular effects, echinocandins generally are the most well tolerated . Rezafungin, a new echinocandin, did not demonstrate an adverse effect on QT interval at therapeutic (600 mg) and supratherapeutic doses (1400 mg) in healthy male and female subjects in this definitive QT/QTc study.…”
Section: Discussionmentioning
confidence: 65%
“…In granulocytopenic patients with invasive candidosis, a higher dose of caspofungin (150 mg/d) led to higher response rates as compared to the standard dose (50 mg/d) 73 . It remains unclear whether patients with IA may benefit clinically from a higher daily dose of caspofungin or do have an increased risk for toxicity (eg cardiac toxicity) 74 …”
Section: Resultsmentioning
confidence: 99%
“…Amphotericin B lipid complex (ABLC) : A retrospective analysis of a large company‐based dataset (Collaborative Exchange of Antifungal Research; CLEAR) showed a 44% efficacy in about 400 patients with IA (55% response in 42 granulocytopenic patients), 31 and 31% response rate in patients after allogeneic stem cell transplantation, 74 mainly in patients with second‐line therapy (BIII). Therefore, ABLC is not regarded as first choice for first‐line therapy of IA (DI).…”
Section: Resultsmentioning
confidence: 99%